Incidencia de las estrategias metodológicas en el desarrollo psicomotriz de los niños-as de 5-6 años de edad del Centro Educativo Particular Mixto Bilingiúe María Del Carmen, Escuela de Educación Básica Zoila Ugarte de Landívar, Escuela de Educación Básica Luis Antonio Aguilar Marin del cantón El Guabo durante el periodo lectivo 2010-2011. - Hidalgo Mite, Karina Johanna (2011)
This research entitled: Impact of methodological strategies in the psychomotor development of children-as 5-6 years old the particular school Bilingual mixed María del Carmen, basic education school Zoila Ugarte De Landivar Luis basic education school Antonio Aguilar Marin of El Guabo canton during the 2010-2011 academic year. It is structured based on the current Guidelines Graduation at the Technical University of Machala.